“Gaze” upon Agricultural Experiences and the Policy Formation Process of Shokuiku: In the Case of JA’s Food and Agriculture Education - NAKAMURA, Mari (Journal of Rural Studies, 2008)
In this paper, l first depict the policy formation process of Shokuiku（Food and Nutrition Education).Shokuiku includes wide contents which are “improved health”, “improved self-sufficiency in food ”and “teaching of a feeling of gratitude”. Especially, the norm of “teaching of a feeling of gratitude” is related to the agricultural experiences. Here l will focus JA’s Food and Agriculture Education that is one of the agricultural experiences. In this thesis, I will analyze it with the concept of the “gaze”. With it, I will examine the effect that the “gaze” from outside gave the actors who offer the agricultural experiences. My subjects are as follows. What kind of identities did they give to their activities? What kind of symbols did they construct? As a result, how did their symbol affect Shokuiku? 　　　To put it concretely, when the Ministry of Education decided on the policy that “zest for living” solves problems around children, the agricultural experiences were “gazed” as the places that can cultivate “zest for living.” JA corresponded to this policy actively and identified JA's Food and Agriculture Education with the symbol of “life”. Then farmers that offered the agricultural experiences co-owned the symbol of “life”, In the policy formation process of Shokuiku influenced the fundamental plan of Shokuiku. At the same time, the diffusion of agricultural experiences was institutionalized as the “educational farms” with a target. The symbol of “life” that was once a symbol in JA became the word which explains Shokuiku of “character formation” symbolically.